Faktor-faktor Yang Mempengaruhi Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Karang Raja Delinom - Neng Yanti Widiyanti (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Iron anemia is anemia that arises due to iron deficiency so that the formation of red blood cells and other functions in the body is disrupted. The purpose of this study was to determine the relationship between the factors that influence the incidence of anemia in pregnant women in the working area of ​​the Karang Raja Delinom Public Health Center. This study used an Analytical Survey using a Cross Sectional approach. The population of this study were pregnant women in the working area of ​​Karang Raja Delinom Public Health Center. The number of samples in this study amounted to 118 respondents. In the univariate analysis, it was found that 118 respondents found that mothers with high risk age were 59 respondents (50.0%) more than mothers with low risk age, namely 59 respondents (50.0%), it was found that mothers with high risk parity were 61 respondents (51.7%) and mothers with low risk parity were 57 respondents (47.3%) and it was found that those who did regular antenatal care were 61 respondents (51.7%) and those who did irregular antenatal care were 57 respondents (47.3%). Bivariate analysis showed that there was a significant relationship between maternal age and the incidence of anemia in pregnant women (p value 0.000), there was a significant relationship between the number of parity and the incidence of anemia in pregnant women (p value 0.002) and there was a significant relationship between the frequency of antenatal care with the incidence of anemia in pregnant women (p value 0.000). The conclusion of this study is that there is a relationship between the factors that influence the incidence of anemia in pregnant women in the working area of ​​the Karang Raja Delinom Public Health Center.